Is Helicobacter pylori eradication required for non-steroidal anti-inflammatory drug-associated erosions and ulcers? - A. Ye. Karateyev; Ye. V. Moroz; Anastasia V. Tsurgan; N. V. Gontarenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To present rational on expediency of Helicobacter pylori (H. pylori) eradication for erosions and ulcers that develop on the background of nonsteroid anti-inflammatory drugs (NSAIDs) therapy. Summary. According to the data of Maastricht consensus (2012), H. pylori infection and NSAIDs are the two major independent etiological factors of peptic ulcer development and upper gastro-intestinal bleeding. However the effect of H. pylori and NSAIDs on gastrointestinal diseases remains uncertain. This is a crucial question as the most of patients (in the Russian population over 50%), that require NSAIDs and low doses of aspirin (LDA) are infected by H. pylori. According to series of studies, H. pylori is significantly more common in patients with NSAID-related gastropathy. H. pylori eradication is capable to decrease the risk of gastrointestinal diseases if carried out prior to NSAIDs prescription. At the same time, severe complicated forms of gastrointestinal diseases are common in H. pylori-negative patients, and H. pylori eradication in patients with NSAID-associated ulcers or ulcer bleeding does not provide essential decrease in recurrence rate at ongoing NSAID intake. In the analysis of large-scale NSAID safety studies no significant difference in endoscopic ulcer rate in the groups of H. pylori-infected and H. pylori-negative patients were detected. Available data allow to conclude that anti-H. pylori therapy requires differential approach in patients with indications for NSAID and LDA treatment. Conclusion. Diagnostics of H. pylori infection and eradication is indicated at development of severe complications (ulcer, bleeding), however they should not be used in routine practice at treatment in patients with low risk of complications. Anyway, H. pylori eradication does not eliminate necessity of other methods for NSAID gastropathy prophylaxis: application of COX-2 selective inhibitors and PPI preventive prescription.